Applying qualitative content analysis to study online support communities - Zaphiris, Panayiotis; Pfeil, Ulrike (My University, 2010)
With the increasing popularity of online support communities for people with disabilities and older people, the research domain of online communities is gaining more and more research potential in the area of inclusive design. There are many studies that investigate social interactions within online communities. However, researchers seem to apply a variety of different methods in very different ways. This makes it often difficult to decide on the appropriate method. In order to provide guidance to researchers in the area of inclusive design, this paper reviews past research in this area and presents a self-contained methodology that is based on qualitative content analysis for studying social interactions in online support communities for people with special needs. A case study from an online community for older people is presented in order to set the theory into context
Keywords: Research; Quality control; Methodology; Communication; Content analysis (Communication); Older people; People with disabilities